Contrast-enhanced ultrasound of the liver: Vascular pathologies and interventions - Safai Zadeh, Ehsan; Prosch, Helmut; Ba-Ssalamah, Ahmed; Scharitzer, Martina; Pochepnia, Svitlana; Findeisen, Hajo; Alhyari, Amjad; Raab, Nils; Huber, Katharina Paulina; Görg, Christian (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Over the past two decades, contrast-enhanced ultrasound (CEUS) has been established as a method complementary to B-mode ultrasound and color Doppler sonography for diagnosing vascular liver pathologies and interventions.The objective of this review is to elucidate the application of CEUS in diagnosing vascular pathologies and interventional procedures.Considering the limitations of ultrasound, CEUS presents a similar alternative to other imaging modalities, such as computed tomography and magnetic resonance imaging, for evaluating vascular pathologies, guiding interventions, identifying complications, and assessing outcomes post intervention. Due to its widespread availability and the absence of radiation exposure, CEUS should be employed as a primary modality.In den letzten zwei Jahrzehnten hat sich die kontrastmittelunterstützte Sonografie (CEUS) als ergänzende Methode zum B-Mode-Ultraschall und zur Farbdoppler-Sonografie bei der Diagnose vaskulärer Leberpathologien und Interventionen etabliert.Ziel dieser Übersicht ist es, die Anwendung der CEUS bei der Diagnose vaskulärer Pathologien und interventioneller Verfahren zu erläutern.Unter Berücksichtigung der Limitationen des Ultraschalls stellt die CEUS eine vergleichbare Alternative zu anderen Bildgebungsverfahren wie der Computertomografie und der Magnetresonanztomografie dar, um vaskuläre Pathologien zu beurteilen und Interventionen zu leiten, Komplikationen zu identifizieren und die Ergebnisse nach der Intervention zu bewerten. Aufgrund der fehlenden Strahlenbelastung und der schnellen Verfügbarkeit sollte die CEUS als primäres Verfahren eingesetzt werden.
Keywords: Ultrasound; CEUS; Liver; vascular pathology; Intervention; Diagnostics